2011
DOI: 10.1007/s00442-011-2030-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen uptake and preference in a forest understory following invasion by an exotic grass

Abstract: Plant-soil interactions have been proposed as a causative mechanism explaining how invasive plant species impact ecosystem processes. We evaluate whether an invasive plant influences plant and soil-microbe acquisition of nitrogen to elucidate the mechanistic pathways by which invaders might alter N availability. Using a (15)N tracer, we quantify differences in nitrogen uptake and allocation in communities with and without Microstegium vimineum, a shade-tolerant, C(4) grass that is rapidly invading the understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 63 publications
(71 reference statements)
2
34
1
Order By: Relevance
“…However, like others (Strickland et al 2010, Kramer et al 2012, we found that microbial biomass (but not microbial activity) was lower under M. vimineum. Previous work suggests that M. vimineum can enhance plot-level N demand by sequestering N in aboveground biomass (Fraterrigo et al 2011). Previous work suggests that M. vimineum can enhance plot-level N demand by sequestering N in aboveground biomass (Fraterrigo et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…However, like others (Strickland et al 2010, Kramer et al 2012, we found that microbial biomass (but not microbial activity) was lower under M. vimineum. Previous work suggests that M. vimineum can enhance plot-level N demand by sequestering N in aboveground biomass (Fraterrigo et al 2011). Previous work suggests that M. vimineum can enhance plot-level N demand by sequestering N in aboveground biomass (Fraterrigo et al 2011).…”
Section: Discussionmentioning
confidence: 98%
“…; Fraterrigo et al . ), and evidence suggests that other plants can benefit from this increased N availability (Fraterrigo et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…At broader scales, such as examined in this study (plots C100 m 2 ), the high levels of resource heterogeneity due to topography, vegetation, light, and edaphic conditions should be conducive for a shade-tolerant invasive . Indeed, when M. vimineum invades and is able to achieve dominance, it may reduce native richness (Adams and Engelhardt 2009;Flory and Clay 2010;Hejda et al 2009), and alter soil chemistry and arthropod communities (Fraterrigo et al 2011;McGrath and Binkley 2009;Simao et al 2010). Consequently, some high diversity plant communities in this region could be jeopardized by detrimental impacts of M. vimineum invasions (Barden 1987;Brewer 2011;Cole and Weltzin 2004;Ehrenfeld et al 2001).…”
Section: Discussionmentioning
confidence: 99%
“…M. vimineum is highly shade tolerant (Winter et al 1982) but can establish in both sunny and shady areas (Cheplick 2010) and both disturbed and undisturbed habitats (Huebner 2010a;Martin et al 2009). Once established, it can become the dominant herbaceous species in invaded areas (Barden 1987;Cole and Weltzin 2005;Redman 2008), altering community composition (Barden 1987;Fairbrothers and Gray 1972), suppressing forest succession Clay 2006, 2010), and changing ecosystem processes (Ehrenfeld et al 2001;Fraterrigo et al 2011;Kourtev et al 1998;Strickland et al 2011). M. vimineum is a prolific seeder (Cheplick and Fox 2011), but seed production is reduced in deep shade relative to high-light environments (Huebner 2010a).…”
Section: Introductionmentioning
confidence: 99%